Frontispiece: Postsynthetic Functionalization of Three‐Dimensional Covalent Organic Frameworks for Selective Extraction of Lanthanide Ions. Issue 21 (15th May 2018) - Lu, Qiuyu; Ma, Yunchao; Li, Hui; Guan, Xinyu; Yusran, Yusran; Xue, Ming; Fang, Qianrong; Yan, Yushan; Qiu, Shilun; Valtchev, Valentin
Abstract : Covalent Organic Frameworks In their Communication on page 6042 ff., Q. Fang, V. Valtchev et al. describe the generation of three‐dimensional (3D) carboxy‐functionalized covalent organic frameworks (COFs) through postsynthetic modification of hydroxy‐functionalized COFs.